Family policies in 'hybrid' welfare states after the crisis: pathways between policy expansion and retrenchment - Blum, S; Formankova, L; Dobrotic, I (Wiley, 2014)
The economic crisis has significantly challenged national welfare states and has often led to retrenchment. The question arises how countries have reacted to the crisis in the area of family policy - not directly connected to rising unemployment and also not as demanding for state spending as for example the pension system. This article analyzes family policy reforms during the crisis in three small European welfare states - Austria, the Czech Republic and Slovenia. Focusing on the 'rationale' behind the reforms, it aims to explore how family policy was affected by the crisis and whether the crisis gave rise to new policy pathways and ideas in the area. The exploratory case studies of reforms conducted in the three countries between 2009 and 2013 show that everywhere the pre-crisis policy pathways were also continued in the period of crisis. The reforms were framed by diverse paradigms related to national-specific contexts along with newly emerged austerity arguments. The Czech Republic shows a continued focus on a neo-liberal paradigm, utilizing the crisis to introduce further residual measures, i.e. mostly negative re-familializing reforms, mixed with de-familializing policies based on the workfare paradigm. Strong crisis-related discourse in Slovenia was accompanied by diverse austerity measures, which strengthened the social dimension of family policy and weakened a de-familialistic effect of the pre-crisis reforms. Austria, much less affected by the crisis, continues to combine social investment and 'freedom of choice' paradigms, introducing an ambivalent amalgam of positive familialistic and de-familialistic family policy reforms. © 2014 John Wiley & Sons Ltd.